Neuromarketing: Strategies for Visual Perception in Predicting Consumer Behavior - Mauricio Quisimalin Santamaria; Alice Garzón Moantaguano; Anabel Parra Jiménez (Estudios de la Gestión, 2025)
The article explores consumers' brain responses to specific visual stimuli to optimize marketing strategies and understand their behavior. Using eye-tracking techniques, it analyzes consumers' reactions to beverage posts on Instagram. The research focuses on three areas of interest: Background (AOI 1), Packaging (AOI 2, including the label), and Linguistic Code (AOI 3), evaluating initial fixations (F1), the duration of the first fixation (F2), and the total number of fixations (F3).